Going the extra mile: Ground-based monitoring of olive ridley turtles reveals Gabon hosts the largest rookery in the Atlantic. (October 2015) - Metcalfe, Kristian; Agamboué, Pierre Didier; Augowet, Eric; Boussamba, Francois; Cardiec, Floriane; Fay, J. Michael; Formia, Angela; Kema Kema, Judicael Régis; Kouerey, Carmen; Mabert, Brice Didier Koumba; Maxwell, Sara M.; Minton, Gianna; et al.
Highlights: First population assessment of Gabon's olive ridley nesting aggregation. Olive ridley nesting effort spans almost the entirety of Gabon's Atlantic coast. Gabon likely hosts the most important rookery for olive ridleys in the Atlantic. Gabon's coastal protected areas contain a considerable proportion of nesting effort. Findings emphasise regional and global importance of Gabon's nesting sea turtles. Abstract: The management of widely dispersed marine vertebrates can be facilitated by better understanding their distribution, density, population trends and threats. Unfortunately, for some populations of sea turtle spatial and temporal data are often lacking, particularly along the Atlantic coast of Africa, a region which is considered globally important. Here we combined spatially limited monitoring data from four nesting beaches over seven seasons with an extensive ground-based coastal survey that covered 585 km of Gabon's Atlantic coast, to provide the first population assessment for the olive ridley turtle Lepidochelys olivacea . This species is currently classified as data deficient by the IUCN in the eastern Atlantic and so is considered a regional conservation priority. Whilst the logistics required to undertake such a comprehensive ground-based census were complicated, the method proved extremely effective in providing population estimates for a widely dispersed marine vertebrate and demonstrates the importance of focusing beyond intensively monitored beaches. In particular, our findings reveal that the presence of nesting activity spans almost the entirety of Gabon's coast, the density of which subsequently reveals that Gabon hosts one of the most important olive ridley rookeries in the Atlantic (2370–9814 clutches, approximating to 948–5452 breeding females per annum and a total estimate of 1422–8178 breeding females), with a significant proportion, 81 ± 3.5% (mean ± 1 S.D.) of total nesting effort occurring within protected areas. These findings thus complement our existing knowledge base and further emphasise the regional and global importance of Gabon's nesting sea turtle populations.